2014
DOI: 10.1175/jtech-d-13-00198.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Turbulent Dissipation Using a Tethered ADCP

Abstract: The structure function method for estimating the dissipation rate of turbulent kinetic energy, previously validated for measurements from seabed fixed mounts, is applied to data from 1.2-MHz acoustic Doppler current profiler (ADCP) instruments operating in pulse-pulse coherent mode and mounted in midwater below a tethered buoy. Movements of the buoy introduce additional relative velocity components, but it is hypothesized that these flow components should not seriously interfere with the turbulence information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…L O , however, increases with e 1=2 so that, at times of significant dissipation, our sampling interval of 5-8 cm should have been adequate. The convincing fits of SF to the r 2=3 form shown in Lucas et al (2014) support this inference.…”
Section: Simpson Et Almentioning
confidence: 62%
See 1 more Smart Citation
“…L O , however, increases with e 1=2 so that, at times of significant dissipation, our sampling interval of 5-8 cm should have been adequate. The convincing fits of SF to the r 2=3 form shown in Lucas et al (2014) support this inference.…”
Section: Simpson Et Almentioning
confidence: 62%
“…Whereas previous ADCP measurements of e in lakes have utilised instruments fixed on a frame sitting on the lake bed, the observations reported here also include data from an ADCP mounted on a buoyant float in mid-water. This mode of operation on a tethered buoy has recently been validated by comparison with a Vertical Microstructure Profiler (VMP) shear probe measurements (Lucas et al 2014) which demonstrated that the motions of the tethered buoy do not compromise the estimation of e because the SF method is based on velocity differences which are not significantly affected by buoy motion. These measurements also confirmed the validity of the constant C v 5 1.45, originally determined from Doppler radar measurements of turbulence in the atmosphere (Sauvageot 1992), for dissipation measurements in water.…”
Section: Dissipation Via the Structure Functionmentioning
confidence: 96%
“…Above 0.7 m elevation, stress estimates became intermittent, with mostly small values punctuated by occasional high‐intensity bursts (e.g., days 156.7 and 158.2, Figures e and f). At these high ( z > 0.7 m) elevations, structure functions [ Wiles et al ., ; Lucas et al ., ] revealed occasional bursts of high‐velocity variance at small (0.015–0.045 m) scales (not shown). These observations might indicate flow disturbance by instruments or the tripod, casting doubt on stresses measured above z = 0.7 m.…”
Section: Overview Of Observationsmentioning
confidence: 99%
“…Structure functions provide spectral information about a range of timescales, as opposed to l and L which provide single correlation scales. Spatial structure functions have also been used to infer energy dissipation rates, as done in Wiles et al [47], Thomson et al [15] and Lucas et al [48]. Fig.…”
Section: Temporal Structure Functionsmentioning
confidence: 99%